Does the Geographic Distribution of Manufacturing Plants Exacerbate Groundwater Withdrawal? -A case study of Hebei Province in China. (10th March 2019) - Zheng, Yanting; Wang, Linjuan; Chen, Hao; Lv, Aifeng
Abstract: The spatial distribution of manufacturing plants has a significant impact on resource use and the environment. This paper examines the impacts of the scattered geographic distributions of manufacturing plants on groundwater withdrawal in Hebei Province, China, which is a region with severe groundwater overexploitation. Instead of using traditional methods to measure urban sprawl, we proposed a factory scatter index (FSI) that incorporates the latitude and longitude of each plant to characterize the degree to which plants are scattered throughout Hebei Province. We also conducted a regression analysis using groundwater withdrawal as the dependent variable, FSI as the independent variable, and other traditional variables as controls. The results reveal that FSI is large in developed regions and has a significant impact on groundwater withdrawal that exceeds impacts from the number of high water-consuming factories in a region, total population, and urbanization. This study highlights the impact of geographically scattered manufacturing plants on water use and may provide a new geographic perspective for regional sustainable development. Highlights: Developed an index to quantitatively describe the spatial distribution of factories. Factories are very highly dispersed in Hebei Province. The scattered distribution of factories exacerbates groundwater withdrawal.